MODELING AND SIMULATION OF LOGISTICS FLOWS : theory and fundamentals. - REVEILLAC, JEAN-MICHEL (JOHN WILEY, 2017)
Volume 1 presents successively an introduction followed by 10 chapters and a conclusion:- A logistic approach- an overview of operations research- The basics of graph theory- calculating optimal routes- Dynamic programming- planning and scheduling with PERT and MPM;- the waves of calculations in a network;- spanning trees and touring;- linear programming - modeling of road traffic.